A rare association between factor H deficiency and lupus: Case report and experimental treatment with curcumin - Lunz Macedo, Ana Catarina; Santisteban Lores, Lazara Elena; Albuquerque, José Antonio Tavares; Duarte, Nilo José Coelho; Romano, Paschoalina; Ebner, Persio Almeida Rezende; Rezende, Vinicius Marcondes; Silva, Clovis A.; Andrade, Luís Eduardo Coelho; Vasconcelos, Dewton Moraes; Isaac, Lourdes (Frontiers in Pediatrics, 2022)
Factor H (FH) is one of the most important regulatory proteins of the alternative pathway of the complement system. FH deficiency is a rare condition that causes unregulated C3 consumption, leading to an increased susceptibility to infections and glomerulopathies. Our previous studies have demonstrated a FH deficient patient carried a c.452G>A, p.R127H FH mutation which leads to a misfolded protein and its retention in the endoplasmic reticulum. In his cultured fibroblasts, FH-delayed secretion was partially rescued when treated with curcumin, and once secreted, exhibited normal regulatory function. Here, we report the child-onset systemic lupus erythematosus (cSLE) in this FH deficient patient and the results of experimental treatment with curcumin aimed to rescue FH secretion and regulatory activity.